KOMPOSIT BIOCHAR MAGNETIK BERBASIS BAMBU SEBAGAI ADSORBEN CONGO RED - Hetharia, I.; Manurung, M.; Suarsa, I W. (Jurnal Kimia (Journal of Chemistry), 2026)
Water pollution caused by Congo red dye waste from the textile industry has driven the development of effective adsorbents that can be easily separated from solution. This study aims to synthesize and characterize a magnetic composite based on Tabah bamboo (Gigantochloa nigrociliata). Biochar was obtained through carbonization of bamboo at 600°C, then modified using iron (III) chloride via alkaline co-precipitation and calcination to form a magnetic composite. Characterization was carried out using FTIR spectroscopy, XRD, and SEM-EDX. The composite was used to adsorb Congo red dye from solution. The results showed that the best composite with a FeCl₃:biochar mass ratio of 3:1 yielded the following characterization results: FTIR spectroscopy showed an Fe–O absorption band at 560–635 cm⁻¹, indicating the formation of iron oxide on the biochar surface. XRD analysis showed 100% crystallinity, confirming the formation of magnetite (Fe₃O₄). SEM-EDX analysis detected an iron element content of 50.58% and showed the strongest magnetic properties. The optimum adsorption conditions were a contact time of 120 minutes, adsorbent mass of 0.025 g, pH 2, and temperature of 30°C. The adsorption process followed the Langmuir isotherm model with a maximum adsorption capacity of 384.62 mg/g. ABSTRAK Pencemaran air akibat limbah zat warna Congo Red dari industri tekstil mendorong pengembangan adsorben yang efektif dan mudah dipisahkan dari larutan. Penelitian ini bertujuan untuk mensintesis dan mengkarakterisasi komposit magnetik berbasis bambu Tabah (Gigantochloa nigrociliata). Biochar diperoleh melalui karbonisasi bambu pada suhu 600 °C, kemudian dimodifikasi menggunakan besi (III) klorida melalui metode kopresipitasi basa dan kalsinasi membentuk komposit magnetik. Karakterisasi dilakukan menggunakan spektroskopi FTIR, XRD, dan SEM-EDX. Komposit digunakan untuk mengadsorpsi zat warna Congo Red dari larutan. Hasil penelitian menunjukkan bahwa komposit terbaik dengan rasio massa FeCl3:biochar 3:1 menghasilkan karakterisasi sebagai berikut: Spektroskopi FTIR menunjukkan pita serapan Fe–O pada 560–635 cm⁻¹ yang mengindikasikan terbentuknya oksida besi pada permukaan biochar. Analisis XRD menunjukkan kristalinitas 100% yang mengonfirmasi terbentuknya magnetit (Fe₃O₄). Analisis SEM-EDX mendeteksi kandungan unsur besi sebesar 50,58%, dan menunjukkan sifat magnetik paling kuat. Kondisi optimum adsorpsi diperoleh pada waktu kontak 120 menit, massa adsorben 0,025 gram, pH 2, dan suhu 30°C. Proses adsorpsi mengikuti model isoterm Langmuir dengan kapasitas adsorpsi maksimum 384,62 mg/g. Kata kunci: biochar, bambu, komposit magnetik, magnetit, congo red, adsorpsi, isoterm Langmuir